FROM THE PHENOMENOLOGY OF TIME TO CHRONOPOLICY - D. G. Gorin (Концепт: философия, религия, культура, 2019)
The article considers the role of the phenomenology of time in substantiating the methodology of chronopolicy. In a phenomenological perspective, chronopolicy appears as a field of knowledge that primarily studies the question of how time determines the constructing of political worlds with their political reflection, political thinking and political action. The political reflection is based on the diverse forms of the political time experience, which determine the conditions for political action. In chronopolitical studies of the political worlds constructing, the fundamental importance is the distinction between the directly contemplated time and the discursively comprehended time. The problem of political subjectivity is considered in the context of the internal “temporal bias” arising because of contradictions between the practical, conscious and experienced forms of time. For example, such a “temporal shift” is manifested in the correlation of the political ideal and the actual political reality. It is the temporalization that helps to resolve the contradictions between the due and the existing in political thinking: the due and the existing are correlated, as a rule, in time. The diverse forms of experience of political time and the ability to manage it largely determine the differences in political reflection of different social strata, groups and communities. These differences are determined by the characteristic social rhythms and ways of giving sense to the past, present and future. The political prospects of the individual political actors depend to a certain extent on their dynamism and sense of time. The chronopolicy becomes more relevant in the conditions of modern culture, which is characterized by the multiplicity of temporality.